Instrumen Investasi Syariah sebagai Determinan Pertumbuhan Ekonomi Indonesia - Gazani, Hawa; Ummah, Afaful; Ilmi, Moh Miqdad; Zahro, Umi Indasyah; Iman, Aldi Khusmufa Nur (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2025)
In recent years, slowing economic growth has necessitated an investment strategy that is not only effective but also sustainable. One emerging option is sharia-compliant investment instruments, which adhere to Islamic principles and are believed to significantly support national economic growth. The primary objective of this study is to analyze the influence of sharia-compliant investment instruments on economic growth in Indonesia. The instruments studied include sharia-compliant mutual funds, sharia-compliant stocks, and sharia-compliant bonds, while economic growth is measured by Gross Domestic Product (GDP). This study uses a quantitative method with the Vector Error Correction Model (VECM) to examine short-term and long-term relationships between variables. Secondary data from quarterly periods from 2011 to 2024 were used as data sources. The results indicate that sharia-compliant mutual funds, both short-term and long-term, have an impact on economic growth, while sharia-compliant stocks and bonds do not significantly influence economic growth. These findings demonstrate the critical role of sharia-compliant mutual funds as an effective investment instrument for advancing national economic growth. However, in order for sharia stocks and sharia bonds to contribute optimally, greater efforts are required.